Associations of COVID-19 risk perception with vaccine hesitancy over time for Italian residents - Caserotti, Marta; Girardi, Paolo; Rubaltelli, Enrico; Tasso, Alessandra; Lotto, Lorella; Gavaruzzi, Teresa (Social science & medicine (1982), 2021)
Many countries were and are still struggling with the COVID-19 emergency. Despite efforts to limit the viral transmission, the vaccine is the only solution to ending the pandemic. However, vaccine hesitancy could reduce coverage and hinder herd immunity. People's intention to get vaccinated can be shaped by several factors, including risk perception which, in turn, is influenced by affect. The present work aimed at investigating how risk perception and some factors associated with the decision to comply with vaccination modulated vaccine acceptance for COVID-19 as compared to seasonal influenza, and how these have varied during the lockdown phases. The study followed the main phases of the emergency in Italy, investigating the intention to get vaccinated against flu and against SARS-CoV-2 (if a vaccine was available) before, during and after the first national lockdown, covering the period from the end of February to the end of June 2020. We investigated the effect of risk perception and other predictors on the decision of getting vaccinated. Compared to the pre-lockdown phase, during the lockdown more people were willing to get vaccinated for COVID-19, regardless of their beliefs about vaccines, and as risk perception increased, so did the intention to accept the vaccine. The acceptance of the flu vaccine increased after the re-opening phase. In addition, the intention to get vaccinated against COVID-19 and against flu increased if there was previous flu vaccination behavior but decreased with increasing doubts about the vaccines in general. The observation of vaccination intentions across the three main phases of the emergency allows important considerations regarding psychological, affect, and demographic determinants useful to tailor public health communication to improve public response to future epidemics. •Acceptance of a COVID-19 vaccine was assessed from February to June 2020 in Italy.•Risk perception is associated with the acceptance of a COVID-19 vaccine.•Hesitancy to vaccinate against COVID-19 decreased during the lockdown.•Acceptance of a COVID-19 vaccine might be hindered by reference to the flu vaccine.